Pengaruh Word of Mouth, Gaya Hidup dan Citra Merek Terhadap Keputusan Pembelian Pada E-commerce Tokopedia - Herlina, Herlina; Suhardi, Suhardi (Ecobuss, 2024)
The research has been done with the purpose of knowing the influence of word of mouth, lifestyle and brand image towards purchase decision on e-commerce Tokopedia partially and simultaneously. The sample was amounted 100 respondents using purposive sampling method, in which the datas was being collected by spreading questionnaire. The testing has been done by using SPSS version 29 application, consists of data quality test, classic assumption test, influence test and hypothesis test. The method that applied in this research was using multiple linear regression method. The result of the research showed that variable word of mouth, lifestyle and brand image partially and simultaneously influence positively and significantly towards purchase decision on e-commerce Tokopedia.